Local knowledge about the Mexican laurel (Litsea glaucescens Kunth) at El Chico National Park, Hidalgo, Mexico - Ortega-Meza, Daniela; Pulido Silva, Maria Teresa; Arruda, Joari Costa de; da Silva, Carolina J.; Sander, Nilo Leal; Gómez Aíza, Adriana (Instituto de Ecología, A.C., 2021)
The Mexican laurel (Litsea glaucescens) is one of the non-timber forest products with the greatest potential in the temperate forests of Mexico. While its ethnobotanical uses are numerous and centuries-old, there is little documented information on traditional knowledge or management of the species. Having this information would help maintain part of the biocultural memory and to apply conservation strategies. The objectives of the study were to document local knowledge and management strategies carried out by peasant communities of the El Chico National Park, as well as to determine harvesting locations and techniques. Fifty-five semi-structured interviews were conducted in the communities of Carboneras and Pueblo Nuevo, in addition to direct observation and visits to the park. All interviewees recognize and use the Mexican laurel, and the majority showed knowledge about the biology of the species. The Mexican laurel is fully integrated into the cultural context of the inhabitants of the protected area. The interviewees are aware of the phenotypic plasticity of the Mexican laurel, notable in its morphology, as well as its aromatic and taste characteristics. Although 9 out of 10 recognize that there are currently legal restrictions on collection it is still carried out at the domestic and commercial level.